An overview of risk factors for androgenetic alopecia among women at Pasar Ambacang, Kuranji, Padang - Sugma, Lidya Aprilia; Yenny, Satya Wydya; Rasyid, Roslaili (UI Scholars Hub, 2023)
Background: Androgenetic alopecia (AGA) is a patterned hair loss due to chronic and progressive miniaturization of hair follicles. Hair represents femininity and self-confidence in women. Therefore, AGA may affect the quality of life and psychology in women. This study aims to describe the risk factors for AGA in women living in Pasar Ambacang Sub-district, Kuranji District, Padang City. Method: This was a descriptive, cross-sectional study that included 40 women with AGA. Interviews with subjects were conducted. This study was approved by the Health Research Ethics Committee at Universitas Andalas (252/UN.16.2/KEPK-FK/2021) Results: AGA was mostly found on patients aged >65 years old (32.5%), married with childbearing (87.5%), overweight (32-5%), had a family history of AGA from the patient’s father (57.5%,) and a family history of AGA from the patient’s mother (75%). According to their medical history, respondents mostly had no hypertension (65%), type-2 diabetes mellitus (DM) (92.5%), and polycystic ovarian syndrome (PCOS) (100%). Most respondents had menarche at (95%), regular menstrual cycles (95%), and were non- menopausal (67.5%). The most common type of AGA was the type I Ludwig Classification (67.5%). Conclusion: Among women, AGA mostly occurred in patients with the following conditions: aged >65 years old, overweight, married with childbearing, had menarche at old, regular menstrual cycles, non- menopausal, and paternal or maternal history of AGA. AGA risk factors, such as hypertension, DM, and PCOS, were slightly found. The most common type of AGA was the type I Ludwig Classification.